2005
DOI: 10.1183/09031936.04.10012704
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary fibrosis in an individual occupationally exposed to inhaled indium-tin oxide

Abstract: Despite the increasing industrial use of indium-tin oxide (ITO) to manufacture flatpanel displays, such as liquid-crystal displays or plasma display panels for televisions, little is known about the potential health hazard induced by occupational exposure to indium compounds.The current study describes a case of fibrotic lung disease that developed after a 4-yr exposure to ITO. The pathology of the lung demonstrated pulmonary fibrosis with the presence of cholesterol granulomas.In conclusion, more attention ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
74
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(83 citation statements)
references
References 13 publications
5
74
2
2
Order By: Relevance
“…Following the first case report involving death 13) , a second case of lung disease related to inhaled ITO was reported in 2005 18) . A worker developed pulmonary fibrosis and emphysema after a 4-yr occupational exposure to ITO.…”
Section: Discussionmentioning
confidence: 99%
“…Following the first case report involving death 13) , a second case of lung disease related to inhaled ITO was reported in 2005 18) . A worker developed pulmonary fibrosis and emphysema after a 4-yr occupational exposure to ITO.…”
Section: Discussionmentioning
confidence: 99%
“…ITO exposure in the work environment generates interstitial pneumonia [1][2][3] . Since indium continues to be used in various industries, it is necessary to clarify the carcinogenicity of indium compounds.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been cases of death due to interstitial pneumonia that are thought to have been caused by indium-tin oxide (ITO) inhalation 1) , and interstitial lung disease has been reported in workers handling ITO [1][2][3] . A recent study reported the carcinogenicity of indium (III) phosphide (InP), which is a compound used in semiconductors, and severe lung damage has also been reported to be associated with other indium compounds as well as InP 4) .…”
mentioning
confidence: 99%
“…In this study, we combined three sets of baseline data, namely data reported by Hamaguchi et al 12) , those reported by Chonan et al 13) , and other newly collected unpublished data, because all three sets of data showed the same consequences. Seven indium lung cases have been discovered [7][8][9][10][11] . Therefore, the consistency of association criterion seems to be fulfilled.…”
Section: Discussionmentioning
confidence: 99%
“…After a detailed medical examination, he was diagnosed with interstitial pneumonia, possibly caused by the inhalation of ITO particles. Up to the end of 2008, seven indium-induced cases of lung injury were disclosed [7][8][9][10][11] . After the first case was found, two epidemiological studies were performed in two different populations of indium-exposed workers 12,13) .…”
mentioning
confidence: 99%